Inverse transition in the dipolar frustrated Ising ferromagnet : the role of domain walls - Araújo Velasque, Luciana; Stariolo, Daniel Adrián; Billoni, Orlando Vito (2021)
Fil: Araújo Velasque, Luciana. Universidade Federal do Rio Grande do Sul. Instituto de Física. Departamento de Física; Brasil.